THE THERAPEUTIC CHALLENGE IN SYSTEMIC TREATMENT OF ADVANCED AND RECCURENT ENDOMETRIAL CANCER - I. Y. Bazaeva; S. V. Khokhlova; A. A. Fedenko (Сибирский онкологический журнал, 2018)
More than 300 000 new cases of endometrial cancer (EC) are registered annually in the world. The prognosis for EC is determined by the stage of the disease. In Russia, stage III–IV EC is diagnosed in 16 % of patients, with the mortality rate in the first year of follow-up of 9.2 %. The management of recurrent/metastatic EC remains a challenging clinical problem. Hormone therapy and chemotherapy is effective in 30 % of patients, with median progression-free and overall survival rates of approximately 6 months and 12 months, respectively. The role of targeted therapy in the treatment of EC remains undefined. However, several studies demonstrated that combination of targeted therapy with chemotherapy resulted in significant improvement in overall survival of patients with advanced endometrial cancer. Published data on the study of checkpoint inhibitors for EC have shown promising results, however, further research is required to more completely understand how the immune system recognizes and eradicated cancer.